My celestial family book 1 : sunshine the star collector - Vitangcol, Ace; Siroy, Jed; Vitangcol, Roy (Las Piñas Alturia Hill Publishing, 2016)
"Ray is a local high school gangster with a heart of gold. This contradiction draws the attention of Sol, a Star Prince who has travelled to Earth to rescue his family. Sol's twelve siblings have been corrupted by dark matter and transformed into Black Stars. In order to save them, Sol needs the help of a Star Knight: a human with a "pure maiden's heart." It just so happens Ray fits the bill, so he is given the Star Bar, a device that allows him to fuse with Stars and gain their celestial powers! As Ray saves each Star, they join him on his quest to rescue the others." Book 1 -- Provided by publisher.
FA-3029g donated by Tepai Pascual.
Keywords: Fantasy comic books, strips, etc -- Philippines; Comic books, strips, etc. -- Philippines; Graphic novels